E-scanner / Mohamad Mustaqim Mohamad Zaki, Mohamad Hassan Mohd Zain and Shah Rezzan Ag Zainal - Mohamad Zaki, Mohamad Mustaqim; Mohd Zain, Mohamad Hassan; Ag Zainal, Shah Rezzan (2018)
The product to be develop is a E-Scanner. This product was propose because that have many issues in the university because of the programmed registration. So the team was choose this product that we believe this product can overcome to that issues. Nowadays, when student attend the programmed, they will long queue to registration their attendance. It will waste their time and so on. The function of this E-Scanner are for the registration process when attend the event or activity. It is efficient ways for apply and use the QR code on their programs or events occur to students by scanning the bar code on their mobile devices So, This product is suitable for used in the programmed registration.